Gelatin-hyaluronic acid injectable hydrogel drug-carrying nanoparticle composite material as well as preparation method and application thereof
By combining gelatin-hyaluronic acid injectable hydrogel drug-loaded nanoparticle composites with enzymatic cross-linking and carnosine modification, the problems of poor drug release sustainability and limited inflammation regulation are solved, achieving the dual therapeutic effects of long-term sustained release and cartilage protection, which is suitable for the local treatment of osteoarthritis.
Patent Information
- Application Number
- CN202510786522.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-12
- Publication Date
- 2025-09-12
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing drug delivery systems have problems in the treatment of osteoarthritis, such as poor drug release sustainability, limited inflammation regulation ability, and lack of cartilage protection function. In particular, the short sustained release time of nanoparticle drugs and the weak mechanical properties of hydrogels make it difficult to achieve long-term stable release and local targeted treatment.
A gelatin-hyaluronic acid injectable hydrogel-loaded drug-loaded nanoparticle composite material is used to form a stable network structure through an enzymatic cross-linking reaction. Combined with carnosine modification, the antioxidant capacity and cartilage tissue affinity are enhanced. The thioether bonds in the nanoparticles respond to the ROS microenvironment to achieve controlled release, synergistically regulating the synovial inflammatory response and protecting chondrocytes.
It achieves long-term sustained release of the drug and dual therapeutic effects, inhibits M1 macrophages, promotes M2 phenotypic transformation, protects chondrocytes, has good biocompatibility and mechanical properties, and is suitable for local precision treatment of osteoarthritis.
Smart Images

Figure CN120617149A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biomedical technology, and in particular to a method for preparing a gelatin-hyaluronic acid injectable hydrogel drug-carrying nanoparticle composite material and its application in the treatment of osteoarthritis. Background Art
[0002] Osteoarthritis is a common, chronic, degenerative joint disease and one of the leading causes of disability among the elderly worldwide. Currently, a stepwise treatment strategy is primarily employed clinically, encompassing primary care, medication, restorative therapy, and joint reconstruction. Pharmacological treatments primarily rely on oral, topical, or intra-articular glucocorticoid administration of nonsteroidal anti-inflammatory drugs (NSAIDs). While these drugs can provide short-term relief of pain and inflammation, they face significant limitations. For example, long-term use of NSAIDs can cause gastrointestinal disturbances and liver and kidney damage. While intra-articular injections offer a promising local therapeutic effect, they are susceptible to rapid clearance by the intra-articular lymphatic system, have a short half-life, and lack targeted delivery, making sustained therapeutic effects difficult to achieve. Furthermore, frequent injections increase the risk of infection. Therefore, the development of a drug delivery system that combines long-lasting sustained release, safety, reliability, and localized targeted therapeutic capabilities is a pressing clinical need.
[0003] Currently, the main types of intra-articular drug delivery systems used include nanoparticles and hydrogels. Nanoparticles can improve drug solubility, stability, and targeting within the inflammatory microenvironment, helping to prolong drug half-life and reduce dosing frequency. Hydrogels, with their well-defined three-dimensional network structure, can significantly prolong drug retention within the joint cavity while also providing lubrication and cushioning. Natural polysaccharide hydrogels, such as gelatin and hyaluronic acid, are particularly popular due to their excellent biocompatibility and biodegradability.
[0004] However, using either nanoparticles or hydrogels alone still presents significant drawbacks. Nanoparticles offer a short sustained release time, typically lasting only 3-5 days. Hydrogels, on the other hand, have weak mechanical properties and, when directly loaded with drugs, exhibit a rapid release rate and a pronounced initial burst, making them difficult to meet the requirements for long-term, stable release. Summary of the Invention
[0005] In response to the problems of existing technologies such as poor drug release sustainability, limited inflammation regulation ability, and lack of cartilage protection function, the present invention proposes a new treatment strategy that integrates sustained and controlled release, dual treatment, good biomechanical properties and injection convenience, providing a more promising solution for the local precision treatment of osteoarthritis. The gelatin-hyaluronic acid injectable hydrogel drug-loaded nanoparticle composite material and its preparation method and application are provided.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: The method for preparing a gelatin-hyaluronic acid injectable hydrogel drug-carrying nanoparticle composite material provided by the present invention comprises the following steps:
[0007] S1. Synthesis of Car-HA: Hyaluronic acid (HA) was covalently linked with adipic acid dihydrazide (ADH) and carnosine (Car) in an EDC / NHS coupling system to prepare the carnosine-modified hyaluronic acid derivative Car-HA.
[0008] S2. Preparation of fenofibrate-loaded nanoparticles (FNPs): Dextran-g-PMEMA, DSPE-PEG-WYRGRL, and fenofibrate (FN) were co-dissolved in DMSO to prepare a mixture. The mixture was slowly added dropwise to deionized water under continuous stirring to induce nanoparticle formation. The suspension was post-treated and filtered to obtain FNPs.
[0009] S3. Preparation of FNPs-GelHA hydrogel: Add the FNPs prepared in step S2 to the gelatin solution and mix thoroughly to obtain a gelatin solution containing FNPs; dissolve the Car-HA prepared in step S1 in PBS buffer to obtain a Car-HA solution; then mix the gelatin solution containing FNPs with the Car-HA solution, add transglutaminase (TGs) to the above mixed system, and perform an enzymatic cross-linking reaction to form a hydrogel FNPs-GelHA with a stable network structure.
[0010] Preferably, in step S1, the specific steps of synthesizing Car-HA are as follows:
[0011] Dissolve 270 mg of hyaluronic acid in 150 mL of deionized water and stir until completely dissolved. Then add the EDC / NHS coupling system: 1.92 g of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC) and 1.6 g of N-hydroxysuccinimide (NHS). Continue stirring to activate the carboxyl groups. Then, add 4.64 g of adipic acid dihydrazide (ADH) and 108 mg of L-carnosine. React overnight at room temperature in the dark for 12-16 hours.
[0012] After the reaction is completed, the mixture is transferred to a dialysis bag with a molecular weight cutoff of 14,000 Da and dialyzed in deionized water for 3 days to remove unreacted small molecules. The dialysis water is replaced regularly during the period. After the dialysis, the product is freeze-dried to obtain carnosine-modified hyaluronic acid Car-HA.
[0013] Preferably, in step S2, the concentration of the mixed solution is: 10 mg dextran-g-PMEMA, 3 mg DSPE-PEG-WYRGRL and 1 mg fenofibrate (FN) are co-dissolved in 1 mL DMSO; then the above mixed solution is slowly added dropwise to 5 mL deionized water to induce the formation of nanoparticles.
[0014] Preferably, in step S2, the post-processing step is specifically as follows: the obtained suspension is transferred into a dialysis bag with a molecular weight cutoff of 3500Da, and dialyzed in deionized water for 24 hours to remove the organic solvent and unencapsulated drugs; the final solution is filtered through a 0.45μm filter membrane to obtain FNPs, which are stored at 4°C for future use.
[0015] Preferably, the preparation method of DSPE-PEG-WYRGRL comprises the following steps: dissolving 2 mg of DSPE-PEG-DBCO and 1 mg of (3-azido)-WYRGRL in 1 mL of dimethyl sulfoxide (DMSO), stirring the mixture at room temperature overnight to generate DSPE-PEG-WYRGRL.
[0016] Preferably, in step S3, the preparation of FNPs-GelHA hydrogel has the following specific reaction parameters: dissolving gelatin at a concentration of 10 wt% in deionized water at 45°C-60°C, cooling to 37°C after complete dissolution, and preparing a gelatin solution; adding the FNPs prepared in step S2 to the gelatin solution at a final concentration of 2 mg / mL, and mixing thoroughly to prepare a gelatin solution containing FNPs;
[0017] The Car-HA prepared in step S1 was dissolved in PBS buffer at a concentration of 1 wt% to prepare a Car-HA solution.
[0018] Preferably, in the enzymatic cross-linking reaction, the gelatin solution containing FNPs and the Car-HA solution are mixed in a volume ratio of 1:1, and transglutaminase (TGs) with a final concentration of 0.5 wt% is added to the mixed system; the enzymatic cross-linking reaction is carried out at 37°C for 3min-6min to form a stable network structure hydrogel FNPs-GelHA.
[0019] A gelatin-hyaluronic acid injectable hydrogel drug-loaded nanoparticle composite material is an FNPs-GelHA hydrogel prepared according to any of the above methods for preparing a gelatin-hyaluronic acid injectable hydrogel drug-loaded nanoparticle composite material.
[0020] A gelatin-hyaluronic acid injectable hydrogel drug-loaded nanoparticle composite material is prepared according to any of the above methods for preparing a gelatin-hyaluronic acid injectable hydrogel drug-loaded nanoparticle composite material to produce a drug-loaded nanoparticle composite material whose carrier is GelHA hydrogel, or a drug-loaded nanoparticle composite material whose drug nanoparticles carried by the injectable hydrogel are FNPs.
[0021] The gelatin-hyaluronic acid injectable hydrogel drug-loaded nanoparticle composite material is used for drug delivery for cartilage-related diseases or for the treatment of cartilage-related diseases.
[0022] The present invention provides a gelatin-hyaluronic acid injectable hydrogel-carrying drug-loaded nanoparticle composite material, as well as its preparation method and application. It has the following beneficial effects:
[0023] (1) The dual-functional gelatin-carnosine modified hyaluronic acid hydrogel GelHA constructed by the present invention is used for the intra-articular delivery of fenofibrate nanoparticles FNPs. The preparation method of this system forms a three-dimensional scaffold with good mechanical properties and good biocompatibility through enzymatic cross-linking induced by transglutaminase. On this basis, carnosine modification enhances its antioxidant capacity and affinity with cartilage tissue, and the thioether bond in FNPs gives it a controlled release property that responds to the ROS microenvironment. The system can continuously release fenofibrate, synergistically regulate the synovial inflammatory response (inhibit M1 macrophages and promote M2 phenotype) and inhibit chondrocyte ferroptosis, thereby achieving a combined therapeutic effect of "anti-inflammatory-protection of chondrocytes". Compared with existing single-function or unstable release delivery systems, the present invention provides a therapeutic platform that is both efficient in inflammation regulation and cartilage protection and has better therapeutic potential.
[0024] (2) The gelatin-hyaluronic acid injectable hydrogel drug-loaded nanoparticle composite material of the present invention, its preparation method and application, and the constructed injectable composite system of gelatin-carnosine modified hyaluronic acid hydrogel (GelHA) composited with fenofibrate nanoparticles FNPs are novel therapeutic strategies integrating sustained and controlled release, dual treatment, good biomechanical properties and injection convenience, providing a more promising solution for the local precision treatment of osteoarthritis, organically integrating the advantages of nanoparticles and hydrogels, coordinating and enhancing the effects, and solving several key problems existing in the existing systems:
[0025] 2.1. Improved sustained-release performance: The thioether bonds introduced into FNPs can respond to the reactive oxygen species (ROS) microenvironment in the joint cavity, achieving controlled drug release; GelHA hydrogel provides a stable three-dimensional scaffold, effectively extending the release time of the drug. The two work synergistically to effectively extend the drug's continued effectiveness at the lesion site.
[0026] 2.2. Dual therapeutic function: The system can continuously release fenofibrate to inhibit M1 macrophages, promote M2 phenotypic transformation, and improve the synovial inflammatory microenvironment. At the same time, it protects chondrocytes by inhibiting ferroptosis of chondrocytes, achieving a synergistic "anti-inflammatory-cartilage protection" treatment.
[0027] 2.3. Taking both mechanical and biological properties into consideration: The present invention uses transglutaminase (TGase) to mildly catalyze the formation of a cross-linked network, which not only improves the mechanical strength of the hydrogel but also ensures excellent biocompatibility and injectability.
[0028] 2.4. Enhanced affinity and antioxidant properties: Carnosine modification improves the hydrogel's affinity for cartilage tissue and antioxidant capacity, helping to build a more stable therapeutic microenvironment. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 . Characterization of FNPs, GelHA and GelHA-FNPs hydrogel prepared in the present invention.
[0030] Figure 2 . For example 2 of the present invention, carnosine modified hyaluronic acid HA in DO 1 H NMR spectrum.
[0031] Figure 3 Characterization of the FNPs, GelHA, and GelHA-FNPs hydrogels prepared in the present invention. (AB) are the particle size and zeta potential of the FNPs measured by dynamic light scattering (DLS); (C) is the transmission electron microscopy (TEM) image of the FNPs in Example 2 of the present invention; (D) is the process of forming the GelHA and GelHA-FNPs hydrogels by transglutaminase enzymatic reaction in Example 3 of the present invention; (E) is the scanning electron microscopy (SEM) image of the freeze-dried GelHA and GelHA-FNPs hydrogels; (F) is a representative compressive stress-strain curve of the GelHA-FNPs hydrogel; (G) is the swelling behavior of the freeze-dried hydrogel in deionized water at different immersion times (n=3); and (H) is the mass retention of the hydrogel after immersion in PBS at 37°C.
[0032] Figure 4 . XPS photoelectron spectra of GelHA and GelHA-FNPs hydrogels.
[0033] Figure 5In vitro biocompatibility evaluation of FNPs-GelHA, including: (A) CCK-8 assay to evaluate the effects of different treatment groups on chondrocyte viability; (B) live / dead cell staining images of chondrocytes in different treatment groups and (C) qualitative analysis results; (D) morphological changes of chondrocytes in different treatment groups; *P<0.05.
[0034] Figure 6 . The anti-ferroptosis effect of FNPs-GelHA in chondrocytes, including (A) the detection results of total ROS and lipid peroxide (Lipid ROS) levels in ATDC5 cells after different treatments; (D, E) semi-quantitative analysis of the detection results in (A); (B) the levels of ferrous ions (Fe) in ATDC5 cells after different treatments 2 +) level detection results; (F) Semi-quantitative analysis of (B); (C) Immunofluorescence detection of GPX4 protein expression levels in ATDC5 cells after different treatments; (G) Semi-quantitative analysis of (C); *P<0.05, **P<0.01, ***P<0.001.
[0035] Figure 7 Figure . Effects of FNPs-GelHA on chondrocyte catabolism, anabolism, and proinflammatory cytokine expression (in vitro experiments). (A-E) RT-qPCR was used to detect the mRNA expression levels of the proinflammatory cytokine IL-6 and catabolism-related factors iNOS, COX2, MMP3, and ADAMTS4 in chondrocytes from different treatment groups. (F-G) Immunofluorescence was used to detect the protein expression of the catabolic factor MMP13 and the anabolic factor type II collagen in chondrocytes from different treatment groups. (H, I) Semi-quantitative analysis of (F) and (G). (J) ELISA was used to detect the expression levels of IL-6 in chondrocytes from different treatment groups (n=3). *P<0.05, **P<0.01, ***P<0.001.
[0036] Figure 8 . In vivo therapeutic effect of FNPs-GelHA; (A) Treatment timeline of DMM mouse model; (B) Representative coronal Micro-CT images of the knee joints of mice in each experimental group; (E) Quantification of osteophyte number based on Micro-CT analysis; (C-D) Histological sections of knee cartilage in each group, stained with H&E and Safranin O-Fast Green, respectively; (F) Modified Mankin score of cartilage degeneration in each group; (G) Representative images of H&E-stained sections of synovium in the knee joints of mice in each group; (H) Synovitis score of each group; *P<0.05, **P<0.01, ***P<0.001.
[0037] Figure 9.Retention time of IR780 fluorescent probe-labeled nanoparticles (NPs) and their loading in GelHA hydrogel in the mouse knee joint; (A) Representative fluorescence images of DMM model mice after intra-articular injection of IR780-NPs or IR780-NPs-GelHA hydrogel at different time points; (B) Changes in relative fluorescence intensity in the mouse knee joint at each time point (n=4); (C) Comparison of the area under the curve (AUC) of each group, ***P<0.001.
[0038] Figure 10 .The therapeutic effect of FNPs-GelHA in vivo; (A) Timeline of the treatment regimen for the DMM mouse model; (B) Representative coronal Micro-CT images of the knee joints of mice in each experimental group; (E) Osteophyte counts based on Micro-CT analysis; (C-D) Representative tissue sections of knee cartilage stained with H&E and Safranin O-fast green, respectively; (F) Modified Mankin score of cartilage degeneration in each group; (G) Representative H&E-stained sections of knee synovium; (H) Synovitis scores in each group; *P<0.05, **P<0.01, ***P<0.001.
[0039] Figure 11 Immunohistochemical analysis of synthesis- and degradation-related proteins and ferroptosis-related factors in the knee cartilage of osteoarthritis DMM mice. (BE) shows the statistical results of each protein in (A); *P < 0.05, **P < 0.01, ***P < 0.001.
[0040] Figure 12 .Routine blood test results and liver function indicators (ALT, AST and ALB) of mice in different treatment groups; the orange dotted lines indicate the normal range of each indicator; abbreviations: RBC: red blood cell; WBC: white blood cell; PLT: platelet; Mon: monocyte; Lymph: lymphocyte; Gran: granulocyte; ALT: alanine aminotransferase; AST: d-aspartate aminotransferase; ALB: albumin.
[0041] Figure 13 .H&E staining results of the heart, liver, spleen, lung and kidney of mice in different treatment groups; scale bar is 50μm. DETAILED DESCRIPTION
[0042] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Unless otherwise specified, the following raw materials are all commercially available products.
[0043] Example 1
[0044] (1) The synthesis method of Car-HA, the specific steps are as follows:
[0045] 270mg of hyaluronic acid HA was dissolved in 150mL of deionized water. After sufficient dissolution, 1.92g of EDC and 1.6g of NHS were added in sequence. Subsequently, 4.64g of dihydrazide adipic acid and 108mg of carnosine (L-Carnosine) were added and reacted overnight at room temperature in the dark. After the reaction was completed, the product mixture was transferred to a dialysis bag with a molecular weight cutoff of 14000Da and dialyzed in deionized water for 3d to remove unreacted substances. The dialysis water was changed regularly during the period. After the dialysis was completed, Car-HA was finally obtained by freeze drying. The product was structurally characterized by hydrogen nuclear magnetic resonance (1H NMR, Bruker Avance 300MHz), proving the successful synthesis of Car-HA.
[0046] Example 2
[0047] (2) Preparation of fenofibrate-loaded nanoparticles (FNPs)
[0048] A method for synthesizing dextran derivatives dextran-g-PMEMA and DSPE-PEG-WYRGRL, wherein the synthesis method of dextran-g-PMEMA is specifically obtained by referring to the preliminary research method in application number ZL202410135597.4, a preparation method for a ROS-responsive nanodrug targeting cartilage and its use.
[0049] The preparation method of DSPE-PEG-WYRGRL comprises the following steps: dissolving 2 mg of DSPE-PEG-DBCO and 1 mg of (3-azido)-WYRGRL in 1 mL of DMSO, stirring the mixture at room temperature overnight, and producing DSPE-PEG-WYRGRL. This product was used directly in subsequent experiments without further purification.
[0050] The synthesis steps for fenofibrate-loaded nanoparticles (FNPs) were as follows: 10 mg of dextran-g-PMEMA, 3 mg of DSPE-PEG-WYRGRL, and 1 mg of FN were dissolved in 1 mL of DMSO. The mixed solution was then slowly added dropwise to 5 mL of deionized water under continuous stirring to induce nanoparticle self-assembly. After post-treatment, the resulting suspension was transferred to a dialysis bag with a molecular weight cutoff of 3500 Da and dialyzed in deionized water for 24 h. The final product was filtered through a 0.45 μm filter membrane to obtain fenofibrate-loaded nanoparticles (FNPs) and stored at 4°C until use.
[0051] Example 3
[0052] (3) Preparation of FNPs-GelHA hydrogel
[0053] Gelatin polymer was dissolved in deionized water at 50°C at a concentration of 10 wt% and cooled to 37°C after dissolution to prepare a gelatin solution. FNPs prepared in Example 2 were added to the gelatin solution at a final concentration of 2 mg / mL to prepare a gelatin solution containing FNPs. Car-HA prepared in Example 1 was dissolved in PBS at a concentration of 1 wt%.
[0054] The gelatin solution containing FNPs was mixed with the Car-HA solution in a volume ratio of 1:1. Subsequently, 0.5 wt% transglutaminase was added to the mixed system and reacted at 37°C for 4 minutes to form the hydrogel FNPs-GelHA.
[0055] Separately, a gelatin solution without FNPs was mixed with a Car-HA solution at a volume ratio of 1:1. Subsequently, 0.5 wt% transglutaminase was added to the mixture and reacted at 37°C for 4 min to form a hydrogel GelHA without FNPs.
[0056] The following is a structural characterization and performance test of the gelatin-hyaluronic acid injectable hydrogel drug-loaded nanoparticle composite material prepared according to the embodiment of the present invention.
[0057] 1. Experimental Methods
[0058] 1.1 Material characterization
[0059] The hydrated particle size and zeta potential of the fenofibrate-loaded nanoparticles (FNNPs) prepared in Example 2 of the present invention were measured using a Zetasizer Nano ZS90 particle size analyzer (Malvern Instruments, Worcestershire, UK).
[0060] The morphology of the nanoparticles was observed using a transmission electron microscope (TEM, JEM-200CX, Japan Electron Optical Laboratory). TEM sample preparation involves dropping the nanoparticle suspension onto a carbon-coated copper grid, allowing it to dry naturally and then staining with phosphotungstic acid for imaging.
[0061] The FNPs-GelHA hydrogel prepared in Example 3 of the present invention was characterized as follows: The micromorphology of the freeze-dried hydrogel was observed using a scanning electron microscope (SEM, MERA3, TESCAN). The sample (8 mm in diameter, 2 mm in height) was freeze-dried and then gold-sprayed.
[0062] The chemical composition of the hydrogels was analyzed using X-ray photoelectron spectroscopy (XPS, Thermo Fisher K-Alpha).
[0063] The mechanical properties were measured using a uniaxial compression tester (Moxi MX-0580) at a loading rate of 5 mm / min.
[0064] The swelling performance was evaluated by immersing the freeze-dried hydrogel samples (8 mm in diameter and 10 mm in height) in deionized water at 37°C. The swelling ratio was calculated using the following formula: Swelling ratio = (WW) / W, where W is the dry weight and W is the wet weight after water absorption.
[0065] Degradation performance was assessed by incubating hydrogel samples in PBS for up to 28 days, with the PBS replaced every three days. The residual weight percentage was calculated as: Residual weight (%) = (W / W) × 100%, where W is the initial dry weight and W is the dry weight after PBS treatment at each time point.
[0066] 1.2 Compatibility test of FNPs-GelHA with chondrocytes
[0067] The cell compatibility of FNPs-GelHA prepared in Example 3 of the present invention with chondrocytes was detected by CCK8 and live-dead staining.
[0068] The CCK8 assay is as follows: chondrocytes (ATDC5 cells) are seeded at 1×10 cells / well in a 96-well plate. 100 μL of culture medium is added to each well, and the plate is placed in a 37°C, 5% CO incubator overnight to allow the cells to adhere and grow. Different concentrations of FNPs, GelHA, and FNPs-GelHA preparations are prepared. The culture medium is discarded, and culture medium containing the different treatment groups is added (100 μL / well). A blank control group (culture medium only) is set up, and the plates are incubated for a further 24 hours. After the treatment period, 10 μL of CCK-8 reagent (adjust the amount according to the reagent instructions) is added to each well and gently shaken to mix. The 96-well plate is then incubated in a 37°C incubator for another 1 hour. Finally, the absorbance (OD value) of each well is measured at a wavelength of 450 nm using a microplate reader.
[0069] Live / dead staining was performed as follows: chondrocytes (3 × 10 cells / well) were seeded in 24-well plates and incubated overnight. Subsequently, the cells were treated with FNPs, GelHA, or FNPs-GelHA containing 10 μM FN for 24 hours. Live / dead cell staining was performed using a Dojindo kit (Japan) containing Calcein-AM and propidium iodide (PI). After staining, cell viability was assessed by fluorescence microscopy.
[0070] 1.3 Quantitative analysis of inflammation- and decomposition-related gene expression
[0071] Chondrocytes (1×10 cells / well) were seeded in 6-well plates and pretreated with FNPs, GelHA, or FNPs-GelHA for 24 hours before being stimulated with IL-1β (10 ng / mL) for another 24 hours. RAW264.7 macrophages were treated similarly and stimulated with LPS (100 ng / mL). Total RNA was extracted using the Tiangen kit, and cDNA was synthesized using TaKaRa's PrimeScript RT Master Mix. Real-time quantitative PCR was performed using a Roche LightCycler 480II and TB Green Premix Ex Taq II. Gene expression levels were analyzed by relative quantification using the 2-ΔΔCt method, using GAPDH as an internal control.
[0072] 1.4 Immunofluorescence
[0073] Chondrocytes (3 × 10 cells / well) were cultured on slides and treated as described above. After fixation and blocking, primary antibodies (MMP13, dilution 1:300; collagen II, 1:400; ACSL4, 1:200) were added and incubated overnight at 4°C. Subsequently, Alexa Fluor 488-conjugated secondary antibodies and Actin-Tracker Red were added for staining. Cell nuclei were counterstained with DAPI. Images were acquired using a confocal microscope. For macrophage polarization, RAW264.7 cells were treated and stained using the same protocol to detect the expression of iNOS and CD206, respectively.
[0074] 1.5 ROS and lipid peroxidation detection
[0075] After treatment and stimulation with IL-1β, chondrocytes were stained with DHE (5 μM) to detect intracellular reactive oxygen species (ROS).
[0076] Lipid peroxidation levels were assessed using the BDP 581 / 591C11 probe. Cells were imaged using fluorescence microscopy and confocal microscopy, respectively.
[0077] 1.6 Intracellular ferrous ion detection
[0078] After chondrocytes were treated as described above, the intracellular Fe 2 The cells were then stained with DAPI for nuclear staining and observed under a fluorescence microscope.
[0079] 1.7 Animal experiments
[0080] All experimental procedures were approved by the Ethics Committee of Peking University Shenzhen Hospital. OA was induced in 8-week-old male C57BL / 6J mice by destabilization of the medial meniscus (DMM). To assess the duration of OA, mice (n = 4 per group) were intra-articularly injected with FNPs or FNPs-GelHA labeled with the near-infrared fluorescent dye IR780, and in vivo imaging was performed using an IVIS Spectrum system (PerkinElmer). For the treatment experiment, mice were randomly divided into five groups (n = 6 per group) and received intra-articular injections of saline, FNPs (containing fenofibrate 36 μg / mL), GelHA, or FNPs-GelHA, starting one week after surgery and continuing every three weeks. Blood samples were collected 10 weeks later for liver function tests (ALT, AST, ALB) and hematological parameters (Mindray BC-2800vet). Major organs and joints were harvested, formalin-fixed, and stained with hematology (HE). Knee joints were analyzed by micro-CT (Vivo 80, Scanco), decalcified, paraffin-embedded, and histologically stained (HE and Safranin O-Fast Green). Aggrecan, type II collagen (Collagen II), matrix metalloproteinase 13 (MMP13), and 4-hydroxynonenal (4-HNE) were detected by immunohistochemistry. The severity of osteoarthritis was assessed using the modified Mankin score.
[0081] 1.8 Statistical analysis
[0082] Data are expressed as mean ± standard deviation (SD). Comparisons between two groups were performed using an unpaired Student's t-test, and multiple group comparisons were performed using one-way ANOVA with Tukey's post hoc test. Statistical significance was set at p ≤ 0.05. All analyses were performed using GraphPad Prism 8.0.2 software.
[0083] 2. Experimental Results and Analysis
[0084] 2.1 Material characterization results
[0085] like Figure 2 Carnosine modified hyaluronic acid HA in DO 1 As shown in the 1H NMR spectrum, the characteristic peaks of HA, ADH, and Car are clearly observed, confirming the successful function of HA and the synthesis of Car-HA prepared in Example 2 of the present invention. Based on the 1H NMR spectrum, the degrees of substitution of ADH and Car on the anhydroglucose unit of HA are 11.8% and 15.2%, respectively.
[0086] Collagen type II-targeted fenofibrate-loaded nanoparticles (FNPs) were prepared by self-assembly of amphiphilic dextran derivatives dextran-g-PMEMA, DSPE-PEG-WYRGRL, and fenofibrate FN in aqueous solution. Figure 3 As shown in Figures A and 3B, the corresponding dynamic light scattering test results show that the average particle size of the nanoparticles is 127.9±1.3nm and the zeta potential is -26.7±0.6mV. Figure 3 As shown in C, transmission electron microscopy observation shows that its morphology is uniform and is a typical spherical structure.
[0087] In order to construct a local drug delivery system, the present invention combines FNPs with Car-HA, gelatin (Gel) and transglutaminase to prepare the FNPs-GelHA hydrogel. Figure 3 As shown in Figure D, after adding 0.5 wt% transglutaminase, both the GelHA and FNPs-GelHA pregel solutions rapidly gelled within 4 minutes at 37°C, forming stable hydrogels. Notably, the addition of FNPs did not alter the gelation kinetics of the hydrogels, with gelation times remaining essentially the same between the two groups.
[0088] like Figure 3 Scanning electron microscopy (SEM) analysis of the freeze-dried hydrogel microstructure (Figure E) revealed that both groups exhibited a porous network structure. The GelHA hydrogel had larger pores, approximately 200-400 μm, while the FNPs-GelHA hydrogel exhibited a denser pore structure, with pore sizes ranging from 50-200 μm. This reduced pore size is attributed to hydrogen bonding interactions between the FNPs and the Car-HA / gelatin matrix.
[0089] In order to further verify the encapsulation of FNPs in hydrogel, X-ray photoelectron spectroscopy (XPS) was used for analysis. Figure 4 The full spectrum shown in A and Figure 4 As shown in the high-resolution Cl 2p spectrum of Figure B, a characteristic Cl 2p peak at 197 eV appeared in the FNPs-GelHA sample, while this peak was not observed in the GelHA control group, further confirming that FNPs were successfully integrated into the hydrogel system, and the loading amount of FNPs in the hydrogel was determined to be 1.8%.
[0090] like Figure 3As shown in Figure F, the mechanical properties of the hydrogel were subjected to a compression test. The macroscopic image shows that when compressed to about 50% of the original height, the FNPs-GelHA hydrogel prepared in Example 3 of the present invention still maintains its complete structure, without obvious cracks or ruptures, and exhibits good toughness. The compressive strength of both the GelHA and FNPs-GelHA hydrogels is about 27 kPa, indicating that although FNPs affects the pore structure, it does not weaken the mechanical strength of the hydrogel. This stable mechanical property is particularly important for intra-articular applications, and helps to achieve buffering, load distribution and cartilage protection functions. As shown in Figure F, the mechanical properties of the hydrogel are very stable and can be used to improve the mechanical properties of the hydrogel. Figure 3 As shown in Figure G, the hydrogels' swelling behavior, a key parameter in tissue engineering, was also evaluated. After immersion in deionized water, both hydrogels reached swelling equilibrium within 8 hours, with final swelling ratios below 8. Compared to hydrogels based on synthetic monomers (such as polyacrylamide), these natural polymer hydrogels prepared and used in this invention exhibit lower swelling capacity and faster equilibrium speed, which is beneficial in avoiding tissue compression caused by excessive expansion during joint repair.
[0091] In addition, if Figure 3 As shown in Figure 3, the in vitro degradation characteristics of the hydrogel were evaluated by incubating in PBS at 37°C for 28 days. The results showed that the residual mass of the GelHA and FNPs-GelHA hydrogels prepared by the present invention was less than 50% of the initial mass after 28 days, and there was no significant difference between the two groups. According to the inferred trend, the hydrogel will be completely degraded within about two months. In the early stage of implantation, the hydrogel can serve as a lubricating matrix, effectively reducing joint friction and mechanical stimulation; over time, the hydrogel gradually degrades, forming a microenvironment that is conducive to cell infiltration and tissue regeneration, thereby promoting cartilage repair.
[0092] 2.2 Analysis results of biocompatibility test of FNPs-GelHA on chondrocytes
[0093] Biocompatibility is a basic requirement for materials used in the treatment of osteoarthritis (OA). To evaluate the biocompatibility of FNPs-GelHA with chondrocytes, a series of in vitro experiments were performed, including CCK-8 cell proliferation assay, live / dead cell staining, and cell morphology analysis. Figure 5 As shown in A, compared with the untreated control group, the proliferation ability of ATDC5 cells was significantly enhanced after being treated with FNPs, GelHA or FNPs-GelHA for 24 hours. Figure 5 As shown in BC, the live / dead cell staining results showed that the three treatments of FNPs, GelHA or FNPs-GelHA did not cause cytotoxicity to ATDC5 cells. Figure 5As shown in Figure D, the cytoskeleton staining results showed that none of the treatments caused significant changes in the cytoskeleton structure of ATDC5 cells. In summary, the above results indicate that the FNPs-GelHA prepared in the present invention has good biocompatibility with chondrocytes, which is sufficient to support its potential as a safe OA treatment platform.
[0094] 2.3 Anti-ferroptosis properties of FNPs-GelHA
[0095] Ferroptosis is a programmed cell death mode that is dependent on iron and accompanied by excessive lipid peroxidation, which is different from the traditional apoptosis mechanism. In the pathological process of osteoarthritis OA, inflammatory stimulation and oxidative stress can induce ferroptosis in chondrocytes, thereby accelerating the degenerative damage of cartilage. In order to evaluate the anti-ferroptosis potential of the FNPs-GelHA hydrogel prepared by the present invention, several key indicators closely related to chondrocyte ferroptosis were detected, including reactive oxygen species (ROS), lipid ROS and intracellular divalent iron (Fe 2 +) levels, which are hallmark indicators of ferroptosis activity.
[0096] Figure 6 As shown in Figures 6A, 6D, and 6E, under IL-1β stimulation, the levels of total ROS and lipid ROS in ATDC5 cells increased significantly. Whether FNPs or GelHA were treated alone, they could alleviate the increase of ROS induced by IL-1β to a certain extent. It is worth noting that the FNPs-GelHA hydrogel prepared by the present invention showed a stronger inhibitory effect in reducing the levels of ROS and lipid ROS, showing a synergistic antioxidant effect. At the same time, Figure 6 B, 6F show that IL-1β exposure also leads to the intracellular Fe 2 + concentration increased significantly, while FNPs, GelHA and FNPs-GelHA treatments could effectively reduce Fe 2 + level. Among them, the FNPs-GelHA group Fe 2 +The decline was the most significant.
[0097] Glutathione peroxidase 4 (GPX4) is a key antioxidant enzyme that regulates ferroptosis and plays an important role in alleviating lipid peroxidation and maintaining chondrocyte redox homeostasis. Figure 6 As shown in Figures C and 6G, IL-1β significantly inhibited the expression of GPX4 in ATDC5 cells. FNPs, GelHA, and FNPs-GelHA all prevented the downregulation of GPX4, with FNPs-GelHA having the most significant protective effect.
[0098] In summary, FNPs-GelHA exhibited excellent anti-ferroptosis activity by simultaneously reducing ROS generation, inhibiting lipid peroxidation, decreasing intracellular iron accumulation and maintaining GPX4 expression in an inflammatory environment, further confirming its potential application value in the treatment of OA.
[0099] 2.4 The results of the analysis of the FNPs-GelHA prepared in the present invention to protect chondrocytes under inflammatory conditions by regulating anabolism, catabolism and inflammatory response are as follows:
[0100] Cartilage degeneration is a key pathological feature of osteoarthritis (OA), and chondrocytes play a central role in maintaining cartilage structure and function. To evaluate the protective effects of FNPs-GelHA on chondrocytes in an inflammatory environment, we examined its regulation of the expression of genes and proteins related to anabolism, catabolism, and inflammation.
[0101] like Figure 7 As shown in A-7E, IL-1β stimulation significantly upregulated the mRNA expression levels of inflammatory factors (IL-6, iNOS, and COX2) and catabolic enzymes (MMP3 and ADAMTS4) in ATDC5 cells. After treatment with FNPs, GelHA, or FNPs-GelHA, the expression of these inflammatory and catabolic factors was significantly downregulated, with the FNPs-GelHA group showing the most significant inhibitory effect. Consistent with the mRNA results, ELISA assays showed that IL-1β significantly promoted the secretion of IL-6 protein. Figure 7 As shown in F, FNPs, GelHA and FNPs-GelHA can all effectively inhibit the upregulation of IL-6, and FNPs-GelHA has the strongest inhibitory effect.
[0102] Further immunofluorescence analysis showed that IL-1β stimulation led to a significant increase in MMP13 expression and a significant decrease in type II collagen (Col II) levels in ATDC5 cells. Figure 7 As shown in G-7H, FNPs, GelHA, and FNPs-GelHA treatments could reverse the above changes by downregulating MMP13 expression and restoring Col II synthesis, thereby slowing down cartilage degradation. Among them, the regulatory effect of the FNPs-GelHA group was the most significant.
[0103] In summary, the FNPs, GelHA, and FNPs-GelHA prepared in this invention all significantly alleviated chondrocyte catabolism and inflammatory responses under inflammatory conditions, while simultaneously enhancing their anabolic activity. FNPs-GelHA, in particular, demonstrated synergistic effects in these multiple regulatory actions, demonstrating its superior therapeutic potential for OA cartilage protection and the prevention and treatment of inflammatory degeneration.
[0104] 2.5 Regulatory effect of FNPs-GelHA on macrophage polarization
[0105] Macrophage polarization plays a key role in regulating the inflammatory microenvironment of joints. This study evaluated the effects of FNPs-GelHA on macrophage polarization. Immunofluorescence staining was used to examine the expression of inducible nitric oxide synthase (iNOS), a marker for pro-inflammatory M1 macrophages, and CD206, a marker for anti-inflammatory M2 macrophages.
[0106] like Figure 8 As shown in A-8D, lipopolysaccharide (LPS) stimulation significantly induced iNOS expression in RAW264.7 macrophages, indicating the occurrence of M1 polarization. FNPs-GelHA treatment significantly downregulated iNOS expression and upregulated CD206 expression, demonstrating that the FNPs-GelHA prepared by the present invention has the ability to inhibit M1 polarization and promote M2 phenotypic conversion.
[0107] To further verify its regulatory effect, the mRNA expression levels of key pro-inflammatory factors (IL-6, TNF-α) and iNOS in RAW264.7 cells stimulated by LPS were detected by RT-qPCR. Figure 8 As shown in E-8G, LPS significantly upregulated the expression of the above three genes, while the FNPs-GelHA treatment group significantly inhibited their expression. Figure 8 As shown in Figure 3, ELISA test results showed that LPS significantly promoted the secretion of IL-6 protein, while FNPs-GelHA treatment significantly reduced the secretion level of IL-6.
[0108] In summary, FNPs-GelHA can effectively regulate the transformation of macrophages from the pro-inflammatory M1 type to the anti-inflammatory M2 type, thereby helping to alleviate the inflammatory response and promote the repair of OA lesion tissue, showing good immunomodulatory potential.
[0109] 2.6 NPs-GelHA retention time in the joint cavity in vivo detection data structure
[0110] The retention time of therapeutic drugs in the joint cavity is an important factor affecting the therapeutic effect of osteoarthritis. To evaluate the retention capacity of this system, nanoparticles (NPs) were labeled with the near-infrared dye IR780 and tracked in real time in vivo using an in vivo imaging system (IVIS).
[0111] like Figure 9As shown in A-9C, the fluorescence signals of the IR780-NPs and IR780-NPs-GelHA groups gradually weakened over time. However, the IR780-NPs group maintained a detectable fluorescence signal within the joint cavity for only 7 days, while the signal of the IR780-NPs-GelHA group persisted for up to 15 days. This result suggests that loading nanoparticles into the GelHA hydrogel significantly prolonged their retention time within the joint cavity, potentially improving therapeutic efficacy by extending local drug exposure.
[0112] 2.7 In vivo therapeutic effect of FNPs-GelHA
[0113] In this study, the DMM (medial meniscectomy) mouse osteoarthritis model was used to evaluate the therapeutic potential of FNPs-GelHA. The specific experimental schedule is as follows: Figure 10 As shown in A. Starting one week after surgery, FNPs-GelHA was injected into the joint cavity every three weeks, and tissues were collected for relevant analysis ten weeks after surgery. Figure 12 As shown in the results, there was no significant difference in complete blood count (CBC) and liver function indexes (ALT, AST, ALB) among the control group, DMM group, FNPs group, GelHA group and FNPs-GelHA group, indicating good systemic biocompatibility. Figure 13 As shown, HE staining results of major organs also showed no obvious pathological changes or inflammatory lesions, further confirming the biosafety of FNPs-GelHA.
[0114] like Figure 7 B and Figure 7 As shown in Figure E, Micro-CT analysis showed that osteophyte formation was significantly increased in the DMM group, while FNPs, GelHA, and FNPs-GelHA treatments all significantly reduced osteophyte formation, with FNPs-GelHA having the most significant inhibitory effect. Figure 10 C and Figure 10 As shown in D, histological evaluation (HE staining and safranin-hematoxylin-fast green staining) showed that the cartilage in the DMM group was severely damaged. All three treatments improved the structural integrity of the cartilage, among which the FNPs-GelHA group had the best protective effect.
[0115] like Figure 10 As shown in Figure 5, the modified Mankin score was consistent with the histological observation. The scores of all treatment groups were significantly better than those of the DMM group, and the improvement in the FNPs-GelHA group prepared by the present invention was the most obvious. Figure 10 G and Figure 10 As shown in Figure 3, the DMM group showed synovial thickening, fibrosis and increased inflammatory cell infiltration. The FNPs, GelHA and FNPs-GelHA prepared by the present invention significantly reduced the synovial inflammation score, and the FNPs-GelHA group had the best effect.
[0116] Key synthesis-related proteins in cartilage, such as aggrecan (AGG) and type II collagen (Col II), as well as matrix degradation-related protein matrix metalloproteinase 13 (MMP13) are important indicators for evaluating the metabolic status of cartilage. Figure 11 As shown in A-11D, immunohistochemical analysis showed that the expression of AGG and Col II in the DMM group decreased significantly, while the expression of MMP13 increased significantly. The FNPs, GelHA and FNPs-GelHA treatments prepared by the present invention reversed the above changes, among which the FNPs-GelHA group showed the strongest effect of promoting cartilage matrix synthesis and inhibiting matrix degradation. In addition, 4-hydroxynonenal (4-HNE) is an important product of lipid peroxidation. The oxidative stress induced by the DMM model promotes the accumulation of 4-HNE, aggravating cartilage degeneration and osteophyte formation. Figure 8 As shown in A and E, the expression of 4-HNE in the cartilage of the DMM group was significantly increased, and FNPs-GelHA treatment significantly inhibited the expression of 4-HNE, protecting the articular cartilage.
[0117] In summary, FNPs-GelHA not only effectively reduces bone and joint structural damage, but also regulates inflammation and oxidative microenvironment, showing good potential for the treatment of osteoarthritis.
[0118] Traditional hydrogel materials are mostly based on gelatin, hyaluronic acid, chitosan, etc., and although they have certain gelling ability and biocompatibility, most of them lack active functions such as antioxidant and anti-inflammatory, and cannot directly intervene in the complex pathological environment of OA (such as oxidative stress, overexpression of inflammatory factors), and the therapeutic effect is limited. The present invention covalently couples L-carnosine with antioxidant properties to the hyaluronic acid molecular chain through the EDC / NHS activation reaction, and successfully prepares Car-HA, which not only retains the good biocompatibility and injectability of HA, but also introduces the free radical scavenging ability of carnosine, thereby giving the hydrogel antioxidant function, which helps to alleviate the oxidative stress environment in the osteoarthritis joint cavity.
[0119] Furthermore, Car-HA and gelatin rapidly cross-link at physiological temperature (37°C) using transglutaminase to form a hydrogel. This process is gentle, safe, and produces no toxic byproducts, making it easy for clinical applications. The gel formation time is controlled within minutes, facilitating rapid gelation and precise positioning after intra-articular injection.
[0120] In summary, the gelatin-hyaluronic acid injectable hydrogel drug-loaded nanoparticle composite material of the present invention, its preparation method, and its application, compared with existing single-function or unstable release delivery systems, the present invention provides a highly efficient treatment platform that takes into account both inflammation regulation and cartilage protection, showing better therapeutic potential. The Car-HA and FNPs synergistic hydrogel strategy proposed in the present invention has good structural adjustability and drug adaptability, and is suitable for the delivery of a variety of anti-inflammatory, antioxidant, and cartilage repair drugs. It can be widely used in the local precision treatment of cartilage-related diseases such as osteoarthritis and rheumatoid arthritis.
[0121] The above are merely embodiments of the present invention. For example, in step S3, the preparation of FNPs-GelHA hydrogel, dissolving gelatin at a concentration of 10 wt% in deionized water at 45°C-60°C, and conventional changes in the storage temperature of the materials in each step can all achieve the gelatin-hyaluronic acid injectable hydrogel drug-loaded nanoparticle composite material of the present invention, its preparation method, and application.
[0122] The above description is only a preferred specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, who makes equivalent replacements or changes based on the technical solution and inventive concept of the present invention, should be covered by the scope of protection of the present invention.
Claims
1. A method for preparing a gelatin-hyaluronic acid injectable hydrogel drug-loaded nanoparticle composite material, characterized in that: The steps are as follows: S1. Synthesis of Car-HA: Hyaluronic acid was covalently linked with dihydrazide adipic acid and carnosine in an EDC / NHS coupling system to prepare the carnosine-modified hyaluronic acid derivative Car-HA. S2. Preparation of fenofibrate-loaded nanoparticles: Dextran-g-PMEMA, DSPE-PEG-WYRGRL, and fenofibrate were co-dissolved in DMSO to prepare a mixture; the mixture was slowly added dropwise to deionized water under continuous stirring to induce nanoparticle formation. The suspension was post-treated and filtered to obtain FNPs; S3. Preparation of FNPs-GelHA hydrogel: Add the FNPs prepared in step S2 to the gelatin solution and mix thoroughly to obtain a gelatin solution containing FNPs; dissolve the Car-HA prepared in step S1 in PBS buffer to obtain a Car-HA solution; then mix the gelatin solution containing FNPs with the Car-HA solution, add transglutaminase to the above mixed system, carry out an enzymatic cross-linking reaction, and form an FNPs-GelHA hydrogel with a stable network structure.
2. The method for preparing a gelatin-hyaluronic acid injectable hydrogel drug-loaded nanoparticle composite material according to claim 1, characterized in that: In step S1, the specific steps of Car-HA synthesis are as follows: Dissolve 270 mg of hyaluronic acid in 150 mL of deionized water and stir until completely dissolved. Then add the EDC / NHS coupling system: 1.92 g of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and 1.6 g of N-hydroxysuccinimide, and continue stirring to activate the carboxyl groups. Then, add 4.64 g of dihydrazide adipic acid and 108 mg of L-carnosine, and react overnight at room temperature in the dark for 12-16 hours. After the reaction is completed, the mixture is transferred to a dialysis bag with a molecular weight cutoff of 14,000 Da and dialyzed in deionized water to remove unreacted small molecules. After the dialysis, the product is freeze-dried to obtain carnosine-modified hyaluronic acid Car-HA.
3. The method for preparing a gelatin-hyaluronic acid injectable hydrogel drug-loaded nanoparticle composite material according to claim 1, characterized in that: In step S2, the concentration of the mixed solution is: 10 mg dextran-g-PMEMA, 3 mg DSPE-PEG-WYRGRL and 1 mg fenofibrate are co-dissolved in 1 mL DMSO; then the above mixed solution is slowly added dropwise to 5 mL deionized water to induce the formation of nanoparticles.
4. The method for preparing a gelatin-hyaluronic acid injectable hydrogel drug-loaded nanoparticle composite material according to claim 3, characterized in that: In step S2, the post-processing step is specifically as follows: the obtained suspension is transferred into a dialysis bag with a molecular weight cutoff of 3500Da, and dialyzed in deionized water to remove the organic solvent and unencapsulated drugs; the final solution is filtered through a 0.45μm filter membrane to obtain FNPs.
5. The method for preparing a gelatin-hyaluronic acid injectable hydrogel drug-carrying nanoparticle composite material according to claim 3, characterized in that: The preparation method of the DSPE-PEG-WYRGRL comprises the following specific steps: dissolving 2 mg of DSPE-PEG-DBCO and 1 mg of (3-azido)-WYRGRL in 1 mL of DMSO, stirring the mixture at room temperature overnight to generate DSPE-PEG-WYRGRL.
6. The method for preparing a gelatin-hyaluronic acid injectable hydrogel drug-carrying nanoparticle composite material according to claim 1, characterized in that: In step S3, the FNPs-GelHA hydrogel is prepared with the following specific reaction parameters: gelatin is dissolved at a concentration of 10 wt% in deionized water at 45°C-60°C, and after complete dissolution, it is cooled to 37°C for standby use to obtain a gelatin solution; the FNPs prepared in step S2 are added to the gelatin solution at a final concentration of 2 mg / mL and mixed thoroughly to obtain a gelatin solution containing FNPs; The Car-HA prepared in step S1 was dissolved in PBS buffer at a concentration of 1 wt% to prepare a Car-HA solution.
7. The method for preparing a gelatin-hyaluronic acid injectable hydrogel drug-loaded nanoparticle composite material according to claim 6, characterized in that: In the enzymatic cross-linking reaction, the gelatin solution containing FNPs and the Car-HA solution were mixed in a volume ratio of 1:1, and transglutaminase with a final concentration of 0.5wt% was added to the mixed system; the enzymatic cross-linking reaction was carried out at 37°C for 3min-6min to form a stable network structure FNPs-GelHA hydrogel.
8. A gelatin-hyaluronic acid injectable hydrogel drug-loaded nanoparticle composite material, characterized in that: FNPs-GelHA hydrogel prepared according to the method for preparing a gelatin-hyaluronic acid injectable hydrogel drug-loaded nanoparticle composite material according to any one of claims 1-7.
9. A gelatin-hyaluronic acid injectable hydrogel drug-loaded nanoparticle composite material, characterized in that: According to the method for preparing a gelatin-hyaluronic acid injectable hydrogel drug-loaded nanoparticle composite material according to any one of claims 1-7, a drug-loaded nanoparticle composite material in which the carrier is GelHA hydrogel, or a drug-loaded nanoparticle composite material in which the drug nanoparticles carried by the injectable hydrogel are FNPs.
10. Use of a gelatin-hyaluronic acid injectable hydrogel drug-loaded nanoparticle composite material according to claim 8 or 9, characterized in that: For drug delivery for cartilage-related diseases, or for treatment of cartilage-related diseases.
Citation Information
Patent Citations
Preparation method and application of ROS (reactive oxygen species) response nano-drug for targeting cartilage
CN118045061A
Cited By
Organic framework microgel for relieving osteoarthritis and application thereof
CN121489859A